Testing the TEBOTS model in self-threatening situations: The role of narratives in the face of ostracism and mortality - Rieger, Diana; Schneider, Frank M. (Frontiers in Communication, 2022)
The TEBOTS model predicts that narratives are sought after more often in times of depletion. The present study aimed at expanding this idea by testing whether engagement with narratives is also intensified under self-threatening conditions. Further, we examined whether narratives can serve coping functions. In a 3(Threat: mortality salience vs. ostracism vs. control condition) × 2(Review of the narrative: positive vs. negative) online experiment (N = 228), we tested whether self-threats and the expectation towards the narrative increase entertainment experiences and facilitate self-serving attributions. The results demonstrated that self-threats and a positive review indeed increased the entertainment experience. Narratives could support coping with an existential threat through enhancing self-serving attributions. The findings are discussed in light of the TEBOTS model and its application in the context of self-threats.